A Synchronized Circadian Clock Enhances Early Chondrogenesis. (December 2021) - Alagha, M. Abdulhadi; Vágó, Judit; Katona, Éva; Takács, Roland; van der Veen, Daan; Zákány, Róza; Matta, Csaba
Objective: Circadian rhythms in cartilage homeostasis are hypothesized to temporally segregate and synchronize the activities of chondrocytes to different times of the day, and thus may provide an efficient mechanism by which articular cartilage can recover following physical activity. While the circadian clock is clearly involved in chondrocyte homeostasis in health and disease, it is unclear as to what roles it may play during early chondrogenesis. Design: The purpose of this study was to determine whether the rhythmic expression of the core circadian clock was detectable at the earliest stages of chondrocyte differentiation, and if so, whether a synchronized expression pattern of chondrogenic transcription factors and developing cartilage matrix constituents was present during cartilage formation. Results: Following serum shock, embryonic limb bud–derived chondrifying micromass cultures exhibited synchronized temporal expression patterns of core clock genes involved in the molecular circadian clock. We also observed that chondrogenic marker genes followed a circadian oscillatory pattern. Clock synchronization significantly enhanced cartilage matrix production and elevated SOX9, ACAN, and COL2A1 gene expression. The observed chondrogenesis-promoting effect of the serum shock was likely attributable to its synchronizing effect on the molecular clockwork, as co-application of small molecule modulators (longdaysin and KL001) abolished the stimulating effects on extracellular matrix production and chondrogenic marker gene expression. Conclusions: Results from this study suggest that a functional molecular clockwork plays a positive role in tissue homeostasis and histogenesis during early chondrogenesis.